Pesticides import and health hazards. Central America, 2005 - 2009 - Bravo-Durán, Virya (2015)
Agricultural pesticides imported in Central America were analyzed, for period the 2005-2009 in order to monitor health hazards. The methodology used has already been published for the analysis of the period 2000-2004 (Bravo et al., 2011). During 2005-2009, 353 active ingredients (ai) were imported in an average annual amount of 39 000 ton ai. Fourteen ai imported in quantities ≥ ton ai 2000 accounted for 77% of imports. The biocidal actions most used were fungicides and herbicides. In these actions, the chemical groups most imported were dithiocarbamates and phenoxyacid the fosfonoglicinas and bipyridyls respectively. The imported quantity of hazardous pesticides corresponded to 27% ai with extremely high acute toxicity, 35% with 2 or more topical effects of moderate to severe and 47% with 4 or more chronic effects. Internationally regulated pesticides amounted to 19% of total imports. Guatemala was the country with highest amount of imported pesticides and Costa Rica continued leading indicators such as kg ai / capita kg ai / rural inhabitant kg ai / agricultural worker kg ai / ha farm. Data indicate that populations in Central America continue to be exposed to health dangers of imported pesticides.